Epigenetic modification augments the immunogenicity of human leukocyte antigen G serving as a tumor antigen for T cell-based immunotherapy. (2nd June 2016) - Ishibashi, Kei; Kumai, Takumi; Ohkuri, Takayuki; Kosaka, Akemi; Nagato, Toshihiro; Hirata, Yui; Ohara, Kenzo; Oikawa, Kensuke; Aoki, Naoko; Akiyama, Naoko; Sado, Masatoshi; Kitada, Masahiro; et al.
ABSTRACT: Tumor immune escape has been a major problem for developing effective immunotherapy. The human leukocyte antigen G (HLA-G) is a non-classical MHC class I molecule whose primary function is to protect the fetus from the mother's immune system. While HLA-G is hardly found in normal adult tissues, various tumor cells are known to express it, aiding their escape from the immune system. Thus, HLA-G is an attractive immunotherapy target. CD4 + helper T lymphocytes (HTLs) play an important role in the immune reaction against tumors by assisting in the generation and persistence of CD8 + cytotoxic T lymphocytes (CTLs) or by displaying direct antitumor effects. We report here that HLA-G expression in breast cancer significantly correlates with a poor prognosis. Also, we describe that the MHC class II-binding peptide HLA-G26–40 was effective in eliciting tumor-reactive CD4 + T cell responses. Furthermore, treatment with the DNA methyltransferase inhibitor 5-aza-2′-deoxycytidine increased HLA-G expression in tumors and subsequently enhanced recognition by HLA-G26–40 -specific HTLs. These findings predict that a combination immunotherapy targeting HLA-G together with a DNA methyltransferase inhibitor could be useful against some cancers.